NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI NURUNKON SANAK DI KELURAHAN JUA-JUA KECAMATAN KAYUAGUNG KABUPATEN OGAN KOMERING ILIR - Mela Pratiwi; Yuniar Yuniar; Firmansyah Firmansyah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2022)
Each region has different traditions, one of which is the tradition of nurunkon sanak in Jua-Jua Village, Kayuagung District, Ogan Komering Ilir Regency. In tradition, of course, it has its own meaning and benefits which do not always conflict with Islam. Thus, it is very important to study more deeply the nurunkon kinship tradition from an Islamic point of view to deepen the faith of the Islamic community in the area. The formulation of the problem in this research is what is the tradition of nurunkon sanak in Jua-jua village, Kayuagung sub-district, Ogan Komering Ilir district. How is the process of implementing the nurunkon sanak tradition in Jua-jua Village, Kayuagung District, Ogan Komering Ilir Regency. And what are the values ​​of Islamic education in the tradition of nurunkon sanak in Jua-Jua Village, Kayuagung District, Ogan Komering Ilir Regency. This type of research is field research. The method used in this research is descriptive method with a qualitative approach of case study type. Which data collection through observation, interviews, documentation. And the data analysis technique is descriptive qualitative. The result of this research is that the nurunkon sanak tradition is a hereditary tradition that is carried out in the context of celebration for every 40-day-old born baby. This tradition is carried out as a form of gratitude to Allah SWT for having been blessed with a child.The process of implementing the nurunkon sanak tradition starts from the morning bathing the baby and the baby's mother, after being bathed in a prayer, followed by the reading of yasin, tahlil and prayers for congratulations by P2UKK, eating together, then bringing the baby to the base of the stairs scattering the rice and turmeric. mixed with coins to be fought over by the children who were there, the baby was moved to another house as a symbol of being able to leave the house, the event was over, all guests were allowed to go home.The values ​​of Islamic education in the nurunkon sanak tradition include the moral value, namely gratitude, the worship value, namely sodaqoh and the aqidah value including endeavor, trust and love for the Apostle.